Communication of bad news by nurses in pediatrics: Scope review protocol (Research, Society and Development, 2024)
Objective: To map the characteristics of bad news communication by nurses in pediatrics. Methodology: This is a scoping review, which aims to answer the following research question: “How is the communication of bad news by nurses in pediatrics characterized?” The search will be carried out in 7 databases in addition to national and international repositories of theses and dissertations. The searches carried out will be exported to the Rayyan Intelligent Systematic Review tool, by two reviewers independently and blindly, and, in case of disagreements, these will be resolved by a third reviewer. Data collection will be carried out using a standardized instrument adapted from the Cochrane Data collection form. The final data will be presented descriptively and through tables and graphs. Results: It is expected to map the literature on the characteristics of this communication at its different levels of care, in addition to strengthening nurses' care practice, supporting the planning and execution of their care for children, adolescents and family members when communicating bad news. In addition, the gaps found in this study may contribute to the development of new research, public policies and/or health technologies. Conclusion: This protocol enables the structuring and guidance for the development of the methodological steps of a scoping review on the communication of bad news by nurses in pediatrics, in order to expand the understanding of the topic, through analysis and systematization of evidence and gaps found.